The Authority of the Notary Supervisory Council regarding Unlawful Actions Related to the Notary's Code of Ethics in Making Authentic Deeds - Tiya Nuraini; Amad Sudiro (Dinasti Research, 2024)
The authority of the Notary Supervisory Council in carrying out supervision and guidance in the implementation of the position of Notary has a big influence and aims to ensure that the implementation of the position is in accordance with existing regulations and runs properly. The Notary Supervisory Council also has the authority to follow up on cases related to violations of the notary's position and violations of the code of ethics committed by Notaries, which can cause problems for the public as Notary clients, because the Notary's position is a position that is trusted and delegated by Law Number 2 of 2014 concerning amendments. Based on Law Number 30 of 2004 concerning the Position of Notaries in making Authentic Deeds which produce strong legal evidence, on this basis Notaries are strictly prohibited in the Law on the position of Notary as well as the Notary Code of Ethics Regulations from committing violations in the implementation of making authentic deeds. Apart from that, Notaries are also obliged to have moral ethics that uphold and maintain the dignity of the Notary's position. Currently, it is not uncommon to find Notaries who commit unlawful acts in carrying out their positions, as in one of the cases that occurred with a Notary in Cirebon in District Court Decision Number 83/Pdt.G/2022/Pn Cbn. The research method used is normative legal research which is descriptive analytical in nature. The results of this research show that in carrying out the office of Notary, the authority of the Notary Supervisory Board is the most important element in creating an orderly and proper implementation of the office of Notary in producing legal products in the form of authentic deeds that are valid and have full legal force.